Identifying marine food web homogenization patterns - Xu, Yan; Huo, Xumeng; Jordán, Ferenc; Zhou, Mingliang; Cai, Yanpeng; Sun, Jun (Frontiers in Marine Science, 2023)
Ecosystems become increasingly similar to each other, based on species composition. Despite the inevitability of homogenized ecosystems due to global change, few studies have specifically addressed the identification of homogeneous systems in food webs. This study focuses on identifying different patterns of marine food web homogenization by selecting 41 marine food webs and establishing an indicator system. The research classifies the food webs into seven main types based on three different homogenization processes (I, II, III, IV, V, VI, and VII), with approximately 60.1%, 46.3%, and 61% of the homogenization being structural, functional, and resource homogenization, respectively. It highlights the importance of homogenization processes in marine ecosystems, which are mainly driven by interactions between structural and resource homogenization. The research found that Type V exhibited universality in both temporal and spatial dimensions, while Type III also showed universality when the food webs were dominated by resource homogenization. On the other hand, Type I, which was associated with human activities, showed locality when the food web only manifested structural homogenization. Functional homogenization often occurred alongside structural homogenization, as seen in Type IV and Type VII. Yet, when the food web exhibited functional homogenization (Type II), it was directly linked to human activities over the past 20 years. The research aimed to improve the methodology in terms of (a) identifying different food web homogenization patterns; (b) establishing indicators system to quantify food web homogenization; and (c) clarifying the ecological significance of food web homogenization. The study provided a comprehensive understanding of food web homogenization and its associated risks, which could inform nature-based ecosystem management strategies to mitigate the impacts of future climate change.